The relationships between ACTN3 rs1815739 and PPARA-a rs4253778 gene polymorphisms and athletic performance characteristics in professional soccer players - Bulgay, C.; Cepicka, L.; Dalip, M.; Yildirim, S.; Ceylan, H. I.; Yilmaz, Ö. Ö.; badicu.; Badicu, G.; Cerit, M. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Current research on athletic performance focuses on genetic variants that contribute significantly to individuals` performance. ACTN3 rs1815739 and PPARA-a rs4253778 gene polymorphisms are variants frequently associated with athletic performance among different populations. However, there is limited research examining the pre-and post-test results of some variants of athletic performance in soccer players. Therefore, the presented research is to examine the relationships between the ACTN3 rs1815739 and PPARA-a rs4253778 gene polymorphisms and athletic performance improvement rates in adaptations to six weeks of training in elite soccer players using some athletic performance tests.